Traumatic Ulcer Associated with Iatrogenic Trauma After Basal Cell Adenoma Surgery - Siregar, Fitri Dona; Setiadhi, Riani (TALENTA, 2023)
Traumatic ulcer is an oral cavity lesion characterized by loss of epithelial lining, reaching the lamina propria. This condition presents a single lesion with irregular borders, surrounded by diffuse erythema, and covered with pseudo-membrane. In specific case, the traumatic ulcer was caused by iatrogenic trauma after basal cell adenoma surgery. This case report aimed to discuss the causes of traumatic ulcer. A 39-year-old female was referred to the Oral Medicine Clinic from the Ear, Nose, and Throat Department, complaining of pain in the oral mucosa after basal cell adenoma surgery. On extraoral examination, the facial symmetry was intact along with dry and exfoliative lips. A solitary, oval, yellowish-white intraoral ulcer covered with pseudomembrane, irregular borders surrounded by diffuse erythema on the palate, left buccal mucosa and upper labial mucosa was present. The patient was diagnosed with traumatic ulcer due to iatrogenic trauma after surgery for basal cell adenoma located within the parotid gland that extended to the left palate. The treatment administered comprised instructions to clean the oral cavity using gauze and a cotton stick soaked in 0.2% chlorhexidine gluconate. Additionally, compressing the affected areas with gauze soaked in 0.9% NaCl and applying a thin coating of Vaseline album on the lips were part of the therapeutic measures. Given the iatrogenic nature of traumatic cancer, comprehensive therapy was considered essential to prevent secondary infection and address issues related to speech, appearance, and masticatory functions.